Associations between Macronutrient Intake and Body Composition of Female Adolescent Athletes and Their Fitness Levels - Agus Hariyanto; Gigih Siantoro; Anindya Mar'atus Sholikhah; Yetty Septiani Mustar; Muhammad Farid Ilhamuddin; Afif Rusdiawan; Muhammad Kharis Fajar (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
Adolescent athletes need more nutrient intake than adolescents of the same age due to their high activities, especially during exercise, to avoid disruption in their growth process. The athlete is also required to have a good body composition to achieve optimal performance. This study examined the relationship between body composition and nutrient intake of female adolescent athletes and their fitness level. A cross-sectional study was conducted on 28 female athletes of Tulungagung Training Centre selected using systematic random sampling. Dietary assessment (energy and macronutrient intake) and body composition (FM, FFM) were measured using 2x24 hours food recall and InBody270. The maximal oxygen uptake (VO2max) was measured using Multistage Fitness Test. Independent sample t-test, Mann-Whitney test, and Spearman test were performed using SPSS 25. The results found that most athletes had a lower macronutrient intake, especially energy, carbohydrate, and fat which did not meet the Recommended Dietary Allowance. However, endurance athletes consumed more protein (p=0,044) and fat (p=0,873) than non-endurance athletes. Spearman test revealed a negative correlation between energy intake, fat mass, and VO2max. In general, many athletes consume macronutrients less than the RDA. Dietary intake and body composition in highly trained adolescent female athletes must be optimized and monitored to achieve better performance and physical fitness.